“Rude Tribes and Wild Frontiers”: Treatment of Ethnicity in Chinese Children’s Literature - Fang, Xiangshu; Bi, Lijun (SARE: Southeast Asian Review of English, 2018)
This essay investigates the treatment of ethnicity in Chinese children’s literature, focusing on the portrayal of China’s ethnic minority groups. It considers the construction of minority ethnic identity in various historical contexts, the linguistic implications of such constructions, and also examines these representations in the context of recent economic developments. It argues that representations of ethnicity in Chinese children’s literature reflect an overriding sense of the superiority of Han Chinese culture in terms of the latter’s role in creating national unity and harmony, and also in advancing the notion of the exoticism of minority ethnicities. The essay also attempts to demonstrate the reasons for the persistence of traditional stereotypes in representations of ethnicity in China